Review of Sally Ann Murray’s: Otherwise Occupied by Lisa Julie - Julie, Lisa (WritingThreeSixty, 2021)
Sally Ann Murray is a South African born author. She is the current Chair of the English Department at Stellenbosch University. Otherwise Occupied is her third published volume of poetry; her previous collections are Open Season (2006) and Shifting (2002).